Colour dematerialization in spiritual literature and painting - Sudrajat, Dadang; Piliang, Yasraf Amir; Sanjaya, Tisna; Kusmara, Andriyanto Rikrik (Harmonia: Journal of Arts Research and Education, 2017)
Colour in variety of art expression can be interpreted differently. This study is aiming at analyzing the colour dematerialization of Javanese spiritual literature â€œFalsafah Jeroning Warnaâ€ by Suprapto Kadis and a painting by Ahmad Sadali entitled â€œGunung Masâ€. Research was done by employing qualitative research, while data was collected by observation, interview, discussion, and documentation study. The analysis of meanings in the two art works was done in descriptive way by using the theory and the knowledge of tasawwuf or sufism, the aesthetics, and arts. Results showed that both sufis, Ahmad Sadali and Suprapto Kadis, share similarities in doing dematerialization towards colour. For them, colour was initially taken from nature (the external territory) which then experienced dematerialization when it made contact with inspiration that was created from the internal area (mental). On the other hand, the difference between the two art works lies on an understanding that colour in FJW is naturalistic mimesis in nature, meanwhile, the painting of Ahmad Sadali is naturaly abstract.